The Study on the Action Mechanism of the Jinyingzi (Rosae Laevigatae Fructus)–Qianshi (Euryales Semen) Couplet Herbs on Membranous Nephropathy Based on Network Pharmacology - Tian, Haoyi; Tian, Yun (Chinese medicine and natural products, 2022)
Objective Our objective was to explore the action mechanism of the Jinyingzi (Rosae Laevigatae Fructus)–Qianshi (Euryales Semen) couplet herbs in the treatment of membranous nephropathy (MN) based on network pharmacology.Methods The active ingredients and targets of Jinyingzi (Rosae Laevigatae Fructus) and Qianshi (Euryales Semen) were screened by systematic pharmacology database and analysis platform. Online Human Mendelian Genetic database and GeneCards database were used to retrieve MN-related targets. The active ingredient-related targets and MN disease targets were introduced into Venny 2.1, and Wayne diagram was drawn. The intersection targets were the potential targets of the Jinyingzi (Rosae Laevigatae Fructus)–Qianshi (Euryales Semen) couplet herbs in the treatment of MN. The protein interaction network of potential targets was constructed, and the core targets were screened with String platform. Metascape platform was used for functional enrichment analysis of gene ontology (GO) and pathway enrichment analysis of Kyoto Encyclopedia of Genes and Genomes (KEGG). The “herb-active ingredient-target-pathway” networks were drawn by using Cytoscape software, and the key components, targets, and signaling pathways were screened.Results A total of 8 active ingredients and 193 related targets in Jinyingzi (Rosae Laevigatae Fructus) and Qianshi (Euryales Semen) were screened out; a total of 1,621 targets of MN disease and 105 potential targets for the treatment of MN were obtained in the treatment with Jinyingzi (Rosae Laevigatae Fructus)–Qianshi (Euryales Semen) couplet herbs; 40 core targets were screened by protein–protein interaction network topology analysis; a total of 1,978 results were obtained by GO function enrichment analysis, and 206 signal pathways were obtained by KEGG pathway enrichment analysis and screening. The network topology analysis of “herb-active ingredient-target-pathway” showed that the key components included quercetin, kaempferol, β-sitosterol, etc.; the key targets included protein kinase Bα (AKT), mitogen-activated protein kinase 1 (MAPK1), B-cell lymphoma-2 (BCL2), prostaglandin-endoperoxide synthase 2 (PTGS2), etc.; the key pathways included advanced glycation end product/receptor of AGE signaling pathway, phosphatidyl inositol 3-kinase (PI3K)/AKT signaling pathway, MAPK signaling pathway, hypoxia-inducible factor-1 signaling pathway, Ras signaling pathway, nuclear factor kappa-B (NF-κB) signaling pathway, Toll-like receptors signaling pathway, p53 signaling pathway and vascular endothelial growth factor signaling pathway in the late stage of diabetic complications.Conclusion The Jinyingzi (Rosae Laevigatae Fructus)–Qianshi (Euryales Semen) couplet herbs can regulate PI3K/AKT, MAPK, NF-κB signaling pathways in MN by targeting proteins of AKT1, MAPK8, PTGS2 through key components of quercetin, β-sitosterol, and kaempferol, so as to inhibit the overexpression of inflammatory factors in renal tissues, regulate inflammatory response, and improve renal function.
Keywords: membranous nephropathy; MN; Jinyingzi (Rosae Laevigatae Fructus); Qianshi (Semen Euryales); network pharmacology; action mechanism